2022
DOI: 10.4236/ajps.2022.139081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Source and Dose on Yield and Quality of Strawberry Fruit

Abstract: The purpose of this research is to investigate the effect of potassium fertilization source and dose on productivity and quality parameters of strawberry. The trial was conducted in 2016-2017 at the experimental greenhouse of Hassan II Institute of Agronomy and Veterinary Sciences in Rabat. Strawberry plants of the cultivar "San Andreas" were planted on November 6 th in 12 liter pots equipped with a gravity fertigation system. The experimental design was a split-plot with eight treatment combinations of two po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
0
0
Order By: Relevance
“…Karaca and Pirlak [65] investigated the effects of different strawberry varieties on fruit yield and quality using frigo seedlings in Ere gli conditions and reported the number of fruit per plant in Albion as 9.28 pieces. While our study findings are higher than the fruit number per plant values obtained from the studies using organic fertilizers above, they are compatible with the value in the study of Gecer et al It was concluded that MSWC applications provide a sufficient amount of K, which provides photosynthesis, water and nutrient intake in flower formation, thus increasing the number of fruits, increasing the number of fruits and positively affecting the number of fruits [66,67].…”
Section: Fruit Parameterssupporting
confidence: 89%
“…Karaca and Pirlak [65] investigated the effects of different strawberry varieties on fruit yield and quality using frigo seedlings in Ere gli conditions and reported the number of fruit per plant in Albion as 9.28 pieces. While our study findings are higher than the fruit number per plant values obtained from the studies using organic fertilizers above, they are compatible with the value in the study of Gecer et al It was concluded that MSWC applications provide a sufficient amount of K, which provides photosynthesis, water and nutrient intake in flower formation, thus increasing the number of fruits, increasing the number of fruits and positively affecting the number of fruits [66,67].…”
Section: Fruit Parameterssupporting
confidence: 89%
“…Pemberian pupuk kalium pada stroberi dapat meningkatkan jumlah bunga dan buah stroberi (Nakro et al, 2022). Kalsium berperan dalam peningkatan kualitas buah cabai besar yang meliputi bobot, panjang dan diameter (Rachma dan Suminarti, 2019), serta berpengaruh signifikan dalam peningkatan bobot buah nanas (Karamina et al, 2021).…”
Section: Pendahuluanunclassified